Strengthening the Framework for Post Program Monitoring. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2016)
Post-Program Monitoring (PPM) is an important part of the Fund's safeguards architecture. It provides a framework for closer engagement with members that have substantial outstanding Fund credit but are no longer in a program relationship, and helps identify risks and provide advice on policies that will assist these members in repaying the Fund. The significant expansion in Fund credit since the global financial crisis, much of it through medium-term financing of members with high access levels, puts a premium on this form of monitoring. The design and implementation of the current policy can be strengthened.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: Sri Lanka